Election Smart House Service as a Voter Education Center for Students in Dumai City - Hariyanti Hariyanti; Gigieh Cahya Permady; Filma Alia Sari; Ahmad Eddison (Universitas of Muhammadiyah Makassar, 2023)
Election Smart House (ESH) is an election organizer innovation designed to improve pre-voter political literacy among students. However, the operation and management of the ESH as a community voter education center is not operating well at present. As a voter education center, ESH provides various attractive services, facilities, and programs. The research design employed a qualitative descriptive method. The researcher intended to describe in-depth and thoroughly the ESH service as a voter education center in Dumai City that strives to promote students' political literacy. Observation, interviews, and documentation were employed in the data collection process. The research informants included Dumai City Election Commission commissioners, Dumai City election smart house (ESH) managers, and Dumai City high school civic education teachers. The study results indicate that ESH services consist of (1) the publication of ESH activities in the mass media and (2) an invitation from the General Election Commission of the City of Dumai for the public, community, or school to visit ESH. ESH can serve as a forum where the election community can discuss elections and democracy. Voter education for students through ESH is a strategic step in educating students about election and democratic materials since ESH offers students materials and additional services that attract visitors.